MAN Network Optimization Through EIGRP Dynamic Routing and DUAL Algorithm: A Study Using Cisco Packet Tracer - widiyanto, Wahyu Wijaya (Jurnal Inotera, 2024)
This research examines the optimization of the Metropolitan Area Network (MAN) through the implementation of the Enhanced Interior Gateway Routing Protocol (EIGRP) and the Diffusing Update Algorithm (DUAL) using the Cisco Packet Tracer. The main goal is to improve the efficiency of routing and data management in MAN networks. This study involves designing a network topology with three routers, setting appropriate IP configurations, and implementing EIGRP and the DUAL algorithm. The results show significant improvements in routing efficiency and data management, confirming the importance of selecting appropriate routing protocols and network configurations for MAN network optimization. These findings contribute to network optimization practices, providing important insights for the development of more efficient urban communications infrastructure.